Pulmonary, rhino-orbital and cutaneous mucormycosis caused by Rhizomucor pusillus in an immunocompromised patient - Hadaschik, Eva; Koschny, Ronald; Hallscheidt, Peter; Enk, Alexander; Hartschuh, Wolfgang (Clinical and experimental dermatology, 2011)
The number of patients with haematopoietic malignancies receiving chemotherapy and stem-cell transplantation has increased the incidence of severe opportunistic infections. Systemic fungal infections are of major concern in immunocompromised patients, as these infections are often fatal. We report a case of a patient with acute myeloid leukaemia who developed multiple cutaneous plaques and necrotizing infiltrates in the lungs during chemotherapy. Using real-time PCR on a wax-embedded tissue sample, Rhizomucor pusillus was identified. We provide an overview of the literature on cutaneous mucormycosis and its diagnosis by PCR.